Is Mandatory Ecological Information Disclosure Linked with Real Ecological Performance? Evidence from Gauteng Local Government, South Africa - NYAHUNA, Thomas; DOORASAMY, Mishelle (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022, 2022)
This paper establishes the degree of mandatory ecological information disclosure of eight municipalities in Gauteng province, South Africa and investigates whether greater environmental performers with higher deviation levels reveal additional information regarding their ecological performance. To get a good understanding of the degree of environmental information disclosures of sampled municipalities, a content analysis index grounded on the conservation segment of the Global Reporting Initiative (GRI) procedures was constructed. The findings show a poor degree of ecological disclosure among municipalities in Gauteng, with a mean total of 14.67 out of 100. Additionally, the outcomes divulge a favourable link between ecological disclosure and basic ecological performance, as projected by the stakeholder theory.